Energy filtering transmission electron microscopy and atomistic simulations of tribo-induced hybridization change of nanocrystalline diamond coating. (June 2015) - De Barros Bouchet, M.I.; Matta, C.; Vacher, B.; Le-Mogne, Th.; Martin, J.M.; von Lautz, J.; Ma, T.; Pastewka, L.; Otschik, J.; Gumbsch, P.; Moseler, M.
Abstract: The tribofilm formed on nanocrystalline diamond coating during ultralow friction in presence of water and glycerol lubrication has been studied experimentally by energy filtering transmission electron microscopy (EF-TEM) and electron energy loss spectroscopy (EELS) on focus ion beam (FIB) cross sections. Surprisingly, even under mild tribological conditions, a tribo-induced hybridization change (sp 3 towards sp 2 ) can be clearly detected at the top of the coating resulting in the formation of a 40 nm thick amorphous sp 2 rich carbon layer with embedded diamond nanoparticles less than 5 nm diameter. Classical molecular dynamics simulations of diamond single crystal asperity collisions can explain this finding. Tribochemical amorphization of the contact zone between the colliding diamond grains followed by fracture events at the asperity shoulders produces ultra-nanodiamonds that remain attached to the amorphous carbon phase. An additional atomistic sliding simulation of two ultra-nanocrystalline diamond coatings yields an amorphous sp 2 rich carbon layer that grows at a rate that is comparable to corresponding layers on the softest diamond single crystal surfaces.